EFFICIENCY OF PUBLIC SPENDING FOR EDUCATION WITHIN THE EUROPEAN UNION IN THE CONTEXT OF THE STRATEGIC FRAMEWORK "EDUCATION AND TRAINING 2020" - Ionela, POPA; Camelia, MARIN (Strategii Manageriale, 2014)
Education is universally recognized as one of the foundations of human development and one of the most powerful tools that a society has for poverty reduction, sustainable development in the long term. The world we live in today can be defined as a global arena, a planet increasingly crowded, faced with a real problem - population growth and thus increasing the number of young people, which means educational systems and to able to support them and to answer their needs. Educational policies should reflect the responsibility of building a world based on a more on mutual support. Marginalization, exclusion, ignorance of the rules of democracy and lack of education are factors that may cause the gap between a minority of people are able to find a path to success and a majority that feels manipulated events. Providing everyone access to knowledge, education has the task of helping people understand the world and to understand others. In the context of the Europe 2020 strategy makes in education provides a new strategic framework for European cooperation in education and training, created from his predecessor's work program "Education and Training 2010", "Education and Training 2020". This paper aims to highlight the strategic objectives for the Member States, the implementation of these, and a number of statistics on the efficiency of public spending on education in the European Union.